Awake craniotomy for resection of supratentorial glioblastoma: a systematic review and meta-analysis. Issue 1 (18th September 2020) - Zhang, John J Y; Lee, Keng Siang; Voisin, Mathew R; Hervey-Jumper, Shawn L; Berger, Mitchel S; Zadeh, Gelareh
Abstract: Background: The goal of glioblastoma (GBM) surgery is to maximize the extent of resection (EOR) while minimizing postoperative neurological complications. Awake craniotomy (AC) has been demonstrated to achieve this goal for low-grade gliomas in or near eloquent areas. However, the efficacy of AC for GBM resection has not been established. Therefore, we aimed to investigate the outcomes of AC for surgical resection of GBM using a systematic review and meta-analysis of published studies. Methods: Systematic searches of Ovid MEDLINE, Embase, Cochrane Controlled Register of Controlled Trials, and PubMed were performed from database inception to September 14, 2019 for published studies reporting outcomes of AC for GBM resection. Outcome measures analyzed included EOR and the event rate of postoperative neurological deficits. Results: A total of 1928 unique studies were identified. Fourteen studies reporting 278 patients were included in our meta-analysis. Mean age of patients was 46.9 years (95% confidence interval [CI]: 43.9–49.9). Early and late postoperative neurological deficits occurred in 34.5% (95% CI: 21.9–48.2) and 1.9% (95% CI: 0.0–9.2) of patients, respectively. Pooled percentage of gross total resection (GTR) was 74.7% (95% CI: 66.7–82.1), while the pooled percentage reduction in tumor volume was 95.3% (95% CI: 92.2–98.4). Conclusions: Limited current evidence suggests that the use of AC for resection of supratentorial GBM is associated with a low rate of persistent neurological deficits while achieving an acceptable rate of GTR. Our findings demonstrate the potential viability of AC in GBM resection and highlight the need for further research on this topic.